Unilateral Agenesis of the Internal Carotid Artery in CHARGE Syndrome - Tung-Ming Chang; Yu-Yuan Ke; Woan-Ling Chen; Ming Chen; Albert D. Yang (Pediatrics and Neonatology)
CHARGE syndrome is a multisystemic disorder comprising colobomas, heart defects, choanal atresia, retarded growth and development, genital hypoplasia, ear anomalies and deafness. The CHD7 gene on chromosome 8q12.1 was recently shown to be a major gene involved in the etiology of this syndrome. We describe a girl with CHARGE syndrome who had a novel mutation of CHD7 associated with agenesis of the left internal carotid artery. She had presented with recurrent episodes of photophobia and vomiting since the age of 6 years. Since her symptoms were well controlled by cyproheptadine, migraine-like attacks were considered. CHD7 molecular confirmation in this patient provides further evidence to support the occurrence of a vascular anomaly suggested from animal models of CHARGE syndrome with molecular delineation. We report this case to emphasize the importance of neurologic signs of photophobia and to highlight the broad clinical variability in this pleiotropic disorder.